2022
DOI: 10.1186/s13102-022-00458-6
|View full text |Cite
|
Sign up to set email alerts
|

Five weeks of Yuishinkai karate training improves balance and neuromuscular function in older adults: a preliminary study

Abstract: Background Martial arts training has shown positive impacts on balance and physiological measurements. Further investigation of the contents and feasibility of an effective therapeutic assessment of martial arts is needed in older adults, mainly for future applications and real-world implementation. Methods Sixteen older adults (8 male, 8 female, age 59–90 years), with or without chronic conditions, participated in a preliminary study using 5-weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(137 reference statements)
1
5
0
Order By: Relevance
“…Moreover, found that adapted karate training improved the quality of life and body balance in 50-year-old men. These findings align with a preliminary investigation by Mustafa et al [10], which demonstrated that five weeks of Yuishinkai karate training could improve balance and neuromuscular function in older adults. Further research is needed to determine the long-term effects of hard martial arts training on the functional fitness of older adults, but the findings thus far suggest that these interventions may provide an effective and enjoyable form of exercise for this population.…”
Section: Hard Martial Arts: Karate and Taekwondosupporting
confidence: 91%
“…Moreover, found that adapted karate training improved the quality of life and body balance in 50-year-old men. These findings align with a preliminary investigation by Mustafa et al [10], which demonstrated that five weeks of Yuishinkai karate training could improve balance and neuromuscular function in older adults. Further research is needed to determine the long-term effects of hard martial arts training on the functional fitness of older adults, but the findings thus far suggest that these interventions may provide an effective and enjoyable form of exercise for this population.…”
Section: Hard Martial Arts: Karate and Taekwondosupporting
confidence: 91%
“…Martial arts involve techniques such as displacement and stepping that challenge balance 37 . In previous studies, different other functional movement balance tools like star excursion and/or Y balance test scores were used to predict injuries in NCAA Division 1 athletes 23 , 38 , 39 , however considering the role of balance in judo and also the relationship between single leg stability and the risk of injury 40 , in this research, for the first time SLS, LOS, and KJP as more accurate and laboratory tools were used to check both the balance and proprioception of professional judokas of the national teams.…”
Section: Discussionmentioning
confidence: 99%
“…Dahmen-Zimmer and Jansen (12) showed that 30 sessions of karate training significantly increased one-leg stand duration in participants with Parkinson's disease. A recent study by Mustafa et al (20) showed that 15 sessions of karate kata training enhanced dynamic balance reactions in a group of older adults with or without neurological disorders.…”
Section: Martial Arts Training Enhances Balance Control and Prevents ...mentioning
confidence: 99%
“…In fact, those types of martial arts also involve mindfulness and combine both slow and fast movements in training. Emerging evidence confirms the effectiveness and feasibility of modified karate (12,20) and Tae Kwon Do (21,22) training in improving balance control in healthy middle-aged to older (>40 yr old) adults, as well as older adults with neurological conditions, and children on the autism spectrum. Studies on middle-aged to older adults (55–85 yr old) also show that Wing Chun practice improves upper and lower limb muscular strength (23,24).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation